ANALISIS KEPENTINGAN TIONGKOK TERHADAP ASIA TENGAH MELALUI JALUR SUTRA BARU RUTE DARAT - Eka Desmiari, Ni Wy Pt; Sushanti, Sukma; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2018)
ABSTRACT The emergence of new silk road economic belt can be analyzed by international relations study. T his study attempted to analyze China’s interests towards Central Asia in the path of the new silk road economic belt. This research using two concept, namely: first, the concept of China's grand strategy by Simon Norton explain g that economic belt’s principle is neighborhood policy. Second, the national interest concept by Nuchterlein. Both of concepts help to map China's national interests to Central Asia in new silk road economic belt. The national interests to be achieved by China are: Trade interest, energy security interest, interest to maintain of Xinjiang Province, and the interests of spreading influence and increasing power. There are also many obstacles in the implementation of economic belt, such as: political instability of the partner country, racial and religious differences, three evil-force issues and regional boundary disputes from the countries in the Central Asia r egion.   Keywords : Economic Belt, China, Xinjiang, China’s Grand strategy, National  Interest, Central Asia